Renal primitive neuroectodermal tumor: A rare case with a good prognosis - Chen, Hanmin; Li, Yanmin; Zeng, Qingming; Wu, Gengqing (Frontiers in Surgery, 2023)
Background Renal primitive neuroectodermal tumor (rPNET) has the characteristics of a difficult preoperative diagnosis, a high degree of malignancy, easy early metastasis or postoperative recurrence, a poor prognosis, and so on. However, rPNET that has no metastasis before surgery can have a good survival prognosis only after radical surgical resection. Methods We report the case of a 14-year-old male patient with a renal tumor who underwent open radical left nephrectomy without radiotherapy or chemotherapy before or after surgery, as confirmed by postoperative pathological results. The prognosis was followed up by a regular review of the chest and whole abdomen on CT, hematuria analysis, renal function, and electrolytes according to the guidelines for renal cancer. Results Postoperative pathological results confirmed rPNET; no adjuvant radiotherapy or chemotherapy were performed after surgery; no tumor recurrence or metastasis were observed during the follow-up of nearly 5 years. Conclusions Despite the high degree of rPNET malignancy, patients without metastases before surgery can still obtain a good survival prognosis through timely radical surgery.